Pengaruh Pemberian Aromaterapi Jahe Terhadap Mual Muntah Pasca Operasi dengan Teknik Spinal Anestesi di RS PKU Muhammadiyah Gamping - Rayyan Rahma Dwi Putri Paputungan; Joko Murdiyanto; Istiqomah Rosidah (STIKes Ibnu Sina Ajibarang, 2025)
Nausea and vomiting are common side effects following spinal anesthesia and surgery. If postoperative nausea and vomiting (PONV) are not managed, they can lead to dehydration, electrolyte imbalance, wound dehiscence, and rupture. Efforts to manage nausea and vomiting include pharmacological and non-pharmacological approaches. The use of ginger aromatherapy is a non-pharmacological method to alleviate postoperative nausea and vomiting. To determine the effect of ginger aromatherapy on postoperative nausea and vomiting in patients undergoing spinal anesthesia at PKU Muhammadiyah Gamping General Hospital. This study employed a pre-experimental design with a one-group pretest-posttest approach. The subjects were 57 postoperative patients who received spinal anesthesia, selected using purposive sampling. Nausea and vomiting responses were measured using the Gordon score.. Data analysis was performed using the Wilcoxon Signed Rank Test. The p-value was 0.000, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. This means there is a significant effect of ginger aromatherapy on postoperative nausea and vomiting in patients undergoing spinal anesthesia at PKU Muhammadiyah Gamping Hospital.